Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2175/106143016x14504669769010
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Compounds that Mimic Urban Stormwater Dissolved Organic Nitrogen

Abstract: Stormwater runoff carrying nitrogen can accelerate eutrophication. Bioretention facilities are among low impact development systems which are commonly used to manage urban stormwater quality and quantity. They are, however, not designed to remove dissolved organic nitrogen (DON) and may become a net DON exporter. Adsorption of seven organic nitrogenous compounds onto several adsorbents was examined. Batch adsorption study revealed that coal activated carbon (AC) exhibited the best performance in adsorption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 35 publications
5
17
0
Order By: Relevance
“…Pyrrole was selected as a more hydrophobic, less labile, heterocyclic organic compound to provide a contrast to the other compounds. All of these compounds were also examined by the authors in their previous study on DON batch adsorption; more detailed information on the DON selection procedure, sources, and properties of these compounds can be found in Mohtadi et al (2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pyrrole was selected as a more hydrophobic, less labile, heterocyclic organic compound to provide a contrast to the other compounds. All of these compounds were also examined by the authors in their previous study on DON batch adsorption; more detailed information on the DON selection procedure, sources, and properties of these compounds can be found in Mohtadi et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…Glass columns were packed with a mixture of coal activated carbon (Calgon Carbon, Pittsburgh, Pennsylvania) and quartz sand (US Silica, Frederick, Maryland). According to the batch adsorption study by Mohtadi et al (2017), coal activated carbon (AC) and coconut‐shell AC demonstrated the best performance in DON adsorption among the tested adsorbents. Coal AC, however, possesses larger specific surface area and average pore size (798 m 2 /g and 53.3 Å) compared to coconut‐shell AC (547 m 2 /g and 30.6 Å, Mohtadi et al, 2017), indicating that coal AC would be a better choice for adsorption of large DON molecules.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogen compounds are key components of animal and plant proteins, and essential element for all living organisms (Mohtadi, James, & Davis, ; Peierls, Caraco, Pace, & Cole, ). However, nitrogen pollution in hydrosphere has been pushed to unprecedented height for eutrophication of lakes and rivers all over the world (Ebeling, Timmons, & Bisogni, ; Kim & Novak, ).…”
Section: Introductionmentioning
confidence: 99%